Prevalence of vitamin D deficiency and associated risk of all-cause and cause-specific mortality among middle-aged and older adults in the United States - Wang, Ting-Yi; Wang, Hung-Wei; Jiang, Ming-Yan (Frontiers in Nutrition, 2023)
The prevalence of vitamin D deficiency varied among populations and regions worldwide. Additionally, the association between vitamin D deficiency and health outcomes remained controversial. Our study aimed to investigate the prevalence of vitamin D deficiency and its association with mortality risk among non-institutional middle-aged and older adults in the United States (U.S.). The study population included 11,119 adult participants aged 50-79 years in the 2007-2016 National Health and Nutrition Examination Survey (NHANES). Vitamin D status was divided as ≤ 30 (severely deficient), 30.1-50 (moderately deficient), 50.1-75 (insufficient), 75.1-100 (sufficient), and > 100 nmol/L (very sufficient). NHANES data were linked to National Death Index to ascertain the survival status and cause of death. The population aged 61.5 years (survey-weighted) and 47.9% was male. Among them, 4.6% were severely vitamin D deficient, 15.2% moderately deficient, and 33.6% insufficient. Individuals with higher vitamin D levels tended to be female, older, white people, non-smoker, non-single, more educated, with higher family income, and lower body mass index. During a median follow-up of 97.0 months, a total of 1585 participants died (15.9 per 10,000 person-months). The crude analysis showed that vitamin D deficiency, but not vitamin D insufficiency, correlated to higher all-cause mortality risk. The association remained similar after adjusting for potential confounders, showing that vitamin D deficiency (HR: 1.38, 95% CI 1.15-1.66), but not vitamin D insufficiency (HR: 1.03, 95% CI 0.88-1.20), correlated to higher all-cause mortality risk. In addition, we showed that vitamin D deficiency was an independent risk factor of death from pneumonia (HR: 3.82, 95% CI 1.14-12.86) but not from cardiovascular diseases, cancer, or cerebrovascular diseases. In summary, among middle-aged and older adults in the U.S., nearly 20% were vitamin D deficient. Vitamin D deficiency, but not vitamin D insufficiency, correlated to increased mortality risk.